Fueling Cancer Vaccines to Improve T Cell-Mediated Antitumor Immunity - Hernandez, Rosmely; Malek, Thomas R. (Frontiers in Oncology, 2022)
Cancer vaccines offer the potential to enhance T cell-mediated antitumor immunity by expanding and increasing the function of tumor-specific T cells and shaping the recall response against recurring tumors. While the use of cancer vaccines is not a new immunotherapeutic approach, the cancer vaccine field continues to evolve as new antigen types emerge and vaccine formulations and delivery strategies are developed. As monotherapies, cancer vaccines have not been very efficacious due to pre-existing peripheral- and tumor-mediated tolerance mechanisms that limit T cell function. Over the years, various agents including Toll-like receptor agonists, cytokines, and checkpoint inhibitors have been employed as vaccine adjuvants and immune modulators to increase antigen-mediated activation, expansion, memory formation, and T effector cell function. A renewed interest in this approach has emerged as better neoepitope discovery tools are being developed and our understanding of what constitutes an effective cancer vaccine is improved. In the coming years, cancer vaccines will likely be vital to enhance the response to current immunotherapies. In this review, we discuss the various types of therapeutic cancer vaccines, including types of antigens and approaches used to enhance cancer vaccine responses such as TLR agonists, recombinant interleukin-2 and interleukin-2 derivatives, and checkpoint inhibitors.